Parents in the Neonatal Intensive Care Unit of “Hospital de São João” (Porto, Portugal) - Hercília Guimarães; Beatriz Guedes; Sara Almeida; Manuela Rodrigues; Madalena Ramos; Teresa Maia; Fátima Clemente (Journal of Pediatric and Neonatal Individualized Medicine, 2015)
The birth of a preterm or a sick infant represents a well-known emotional crisis for parents and family. It has been documented that a multidisciplinary approach to the care of newborns hospitalized in Neonatal Intensive Care Units (NICUs) is essential for the development of these children. The presence of parents 24 hours a day, participating in the care of their children, is a reality in our NICU since its opening in July 1983. Aspects related to the optimization of care for these immature newborns, as well as the relationship between parents and professionals, are also mentioned.